A responsabilidade social empresarial, uma questão de cultura: o caso Petrobrás - Santos, Raul César Mello dos (2007)
Corporate social responsibility is a very current theme, its notion has expanded in recent years, and should be discussed broadly in the academy and perceived as an important issue that should be observed and performed in organizations. Therefore, the present work will discuss the mechanisms of disclosure and actions of the corporate social responsibility, in the sense of seeking a relationship between the corporate social responsibility and how the organizational culture is perceived and utilized in the context of social change, objectifying the management of the corporate social responsibility. (CSR). This research discusses the concept of the corporate social responsibility (CSR) and how this practice is incorporated in the company by means of cultural change in the organization, such as a legitimate instrument of social awareness in an oil company. This study searches to identify the perception of the managers and employees of the social responsibilities in the company and if CSR is present in the culture of the organization. The method used in this research is exploratory-descriptive with data collected through qualitive interviews with various directors, managers and employees. This study leaves a challenge for the field of organizational studies to unmask the characteristics of the phenomenon that still requests many studies in Brazil.